Characterization of root-associated fungi and reduced plant growth in soils from a New Mexico uranium mine. (4th March 2023) - Portman, Taylor A.; Granath, Abigail; Mann, Michael A.; El Hayek, Eliane; Herzer, Kelsie; Cerrato, José M.; Rudgers, Jennifer A.
ABSTRACT: Characterizing the diverse, root-associated fungi in mine wastes can accelerate the development of bioremediation strategies to stabilize heavy metals. Ascomycota fungi are well known for their mutualistic associations with plant roots and, separately, for roles in the accumulation of toxic compounds from the environment, such as heavy metals. We sampled soils and cultured root-associated fungi from blue grama grass ( Bouteloua gracilis ) collected from lands with a history of uranium (U) mining and contrasted against communities in nearby, off-mine sites. Plant root-associated fungal communities from mine sites were lower in taxonomic richness and diversity than root fungi from paired, off-mine sites. We assessed potential functional consequences of unique mine-associated soil microbial communities using plant bioassays, which revealed that plants grown in mine soils in the greenhouse had significantly lower germination, survival, and less total biomass than plants grown in off-mine soils but did not alter allocation patterns to roots versus shoots. We identified candidate culturable root-associated Ascomycota taxa for bioremediation and increased understanding of the biological impacts of heavy metals on microbial communities and plant growth.